2013
DOI: 10.2139/ssrn.2293100
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment into Transition Economies: Are the Balkans Different?

Abstract: The paper explores the determination of foreign direct investment (FDI) into the Balkan transition economies -Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Macedonia, Montenegro, Romania and Serbia. Detailed FDI inflows to Southeast Europe (SEE) are analysed to determine the main differences in the volume, timing and sectoral structure of FDI within the region and in comparison to the Central East European countries. A gravity model to all transition economies during 1990-2011 is then estimated to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 29 publications
3
51
1
3
Order By: Relevance
“…Estrin and Uvalic [(2013] found that levels of FDI to Balkan transition economies can be explained by three categories of factors including: the size of the domestic economy in terms of GDP per capita, their distance from the investing economies of Western Europe and their remoteness from the EU and other major trading blocks. Empirical analyses were conducted in various parts of the world, mainly in emerging markets.…”
Section: Hypotheses Buildingmentioning
confidence: 99%
“…Estrin and Uvalic [(2013] found that levels of FDI to Balkan transition economies can be explained by three categories of factors including: the size of the domestic economy in terms of GDP per capita, their distance from the investing economies of Western Europe and their remoteness from the EU and other major trading blocks. Empirical analyses were conducted in various parts of the world, mainly in emerging markets.…”
Section: Hypotheses Buildingmentioning
confidence: 99%
“…The relation depends on the type of the FDI, as horizontal investments may restrain trade, whereas vertical ones may facilitate it, especially with the investing country (Camarero and Tamarit, 2003). Regarding the region of the South-Eastern Europe, Mehić and Babić-Hodović (2011) found positive and statistically important influence of the FDI on exports of the SEEs, which was in a contrary to results of Estrin and Uvalic (2013). …”
Section: Assumptions Of the Imperfect Substitutes Model Imply That Tmentioning
confidence: 93%
“…One of the biggest ones would be an improvement in the institutional quality that these economies lack. The severe effect of this is the increased perception of risk investors have, that ultimately undermines the higher inflow of foreign capital (Estrin and Uvalic, 2013).…”
Section: Policy Implications and Recommendationsmentioning
confidence: 99%